1992
DOI: 10.1017/s0021859600068040
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil type, crop management and weather on the recovery of 15N-labelled fertilizer applied to winter wheat in spring

Abstract: SUMMARY15N-labelled fertilizer was applied, in spring, to winter wheat crops in nine experiments in eastern England over a period of 4 years. Five were on Batcombe Series silty clay loam, two on Beccles Series sandy clay loam (with a mole-drained clay subsoil) and two on Cottenham Series sandy loam. In three of the experiments, different rates of fertilizer N were applied (up to 234 kg N/ha); in the others, a single rate (between 140 and 230 kg/ha) was used.Recovery of fertilizer N in the above-ground crop (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 27 publications
2
47
1
Order By: Relevance
“…According to Chaney (1990), the non-linear effect of N-fertilisation on the nitrate(V) content in soil has environmental and economic implications. Powlson et al (1992) indicate that over-fertilization will not only be wasteful but may also lead to ground and surface water pollution.…”
mentioning
confidence: 99%
“…According to Chaney (1990), the non-linear effect of N-fertilisation on the nitrate(V) content in soil has environmental and economic implications. Powlson et al (1992) indicate that over-fertilization will not only be wasteful but may also lead to ground and surface water pollution.…”
mentioning
confidence: 99%
“…The AzoFert ® model assumes that mineral N in the soil (residual N, mineralised N and fertiliser N) is fully available to the crop both temporally (between the opening of the balance sheet and crop harvest) and spatially (regardless of the distribution of water, nitrogen and roots in the soil profile). This assumption was verified for the N fertilisation of annual crops in northern Europe, where drainage stops at the end of winter and where water availability frequently does not limit N uptake over the growing season [17,18]. However, this condition is not always met in other climates, such as during droughts under Mediterranean conditions or under rainy conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The functions used for N immobilisation and volatilisation of ammonia were derived from 15 N experiments that demonstrated the microbial immobilisation of added fertiliser N and the incomplete recovery of the added N by different crops in the temperate climate of northwestern Europe [17,18].…”
Section: Date Of Application Of Vinasse To Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al (2013) reported that when N application rates increased from 0 to 320 kg ha −1 , NO 3 --N leaching below 100 cm depth increased from 15 to 258 kg ha −1 during the summer fallow, in an experiment on the south of the Loess Plateau, China. The mechanisms of the residual N loss may include nitrate leaching, and denitrification (Powlson et al 1992;Macdonald et al 1997;Ju et al 2009). Further study is needed to estimate the relative contributions of these different loss mechanisms, and measures to control residual N loss during summer fallow are also needed.…”
Section: N Addedmentioning
confidence: 99%